Phlegmonous appendicitis as a variant of uncomplicated appendicitis - Tezcan Akın; Hüseyin Fahri Martlı; Eda Şahingöz; Birkan Birben; Sadettin Er; Ayşe Çiftçi; Hayriye Tatlı Doğan; Mesut Tez (Scientific Reports)
Abstract Acute appendicitis is the most common cause of surgical acute abdomen, and its classification into uncomplicated, phlegmonous, and complicated forms is crucial for guiding treatment strategies. This study aims to compare the preoperative laboratory findings and postoperative outcomes of phlegmonous appendicitis with uncomplicated and complicated appendicitis. This retrospective cohort study included 1,441 patients who underwent appendectomy between January 2019 and March 2021 at Ankara Bilkent City Hospital. Patients were classified based on histopathological findings into four groups: normal appendix, uncomplicated appendicitis, phlegmonous appendicitis, and complicated appendicitis. Preoperative laboratory values, postoperative complications, and length of hospital stay were analyzed. The distribution of patients was as follows: Group A (normal appendix, 7.6%), Group B (uncomplicated appendicitis, 59.8%), Group C (phlegmonous appendicitis, 17.6%), and Group D (complicated appendicitis, 15%). Phlegmonous appendicitis exhibited significantly higher leukocyte counts and appendix diameters compared to uncomplicated appendicitis but had lower CRP values than complicated appendicitis. The median hospital stay was similar for Groups A, B, and C (1 day) but significantly longer for Group D (2.1 days, p < 0,001). Complication rates were highest in Group D (24.1%) compared to the other groups. While phlegmonous appendicitis shares some clinical and laboratory characteristics with complicated appendicitis, its postoperative outcomes align more closely with those of uncomplicated appendicitis. This suggests that phlegmonous appendicitis may be more accurately classified as a variant of uncomplicated appendicitis, emphasizing the need for consistent classification to improve treatment strategies and patient outcomes.